Fine Needle Aspiration Cytology as Primary Diagnostic Tool in Cervical Lymphadenopathy: Systematic Approach Is the Key to Stay Relevant (Case Series) - Khushdeep Kaur Shergill; Sunita Bisht; Hari J Pillai; Vikas Kumar; Neha Rautela; Sumeet Arora; Dayal Singh Bisht (Annals of Pathology and Laboratory Medicine, 2026)
Introduction: Cervical lymphadenopathy is one of the commonest clinical presentations in a number of medical and surgical conditions with final diagnosis varying from a spectrum of reactive lymphadenitis to primary lymphomas. Fine Needle aspiration cytology has been considered as the quick and minimally invasive OPD technique in establishing diagnosis in such cases. With this case series displaying a vast spectrum of diseases presenting as cervical lymph node masses, we aim at discussing a systematic approach to ensure best results with FNAC as the initial primary diagnostic modality for cervical lymphadenopathy and thus ensuring optimum utilization of available resources. Case Presentation: We present a series of six cases which reported to our hospital from Nov 2024 to Oct 2025, displaying a vast spectrum of diseases presenting as cervical lymph node masses, primarily aiming to utilize the cost-effective diagnostic modality of FNAC to achieve best results.Conclusion: In resource constraint scenarios, a quick, easy and minimally invasive investigative technique like FNAC while following a systematic logarithmic approach proves to be diagnostic in most of the cases, hence preventing unnecessary surgical intervention.